Refractory Strongyloides stercoralis hyperinfection syndrome in a chronic alcoholic: a clinical challenge - Mitra, Sona; Bavishi, Ashish; Marathe, Anant; Muley, Arti; Patel, Kavya Kumar (International Journal of Research in Medical Sciences, 2025)
Strongyloides stercoralis is an intestinal nematode capable of causing persistent autoinfection, often leading to asymptomatic or mild gastrointestinal illness. However, in immunocompromised individuals, including those with chronic alcohol use and malnutrition, it can escalate into life-threatening hyperinfection syndrome. We report a diagnostically and therapeutically challenging case of a 56 years old male with a history of chronic alcoholism and malnutrition who presented with profuse diarrhea, generalised weakness and pellagrous dermatitis. Stool microscopy confirmed S. stercoralis infection and oral ivermectin therapy was initiated. Despite initial symptomatic improvement, the patient developed progressive respiratory distress, abdominal distension and cardiovascular instability, culminating in multi-organ dysfunction syndrome (MODS) and death. Notably, peripheral eosinophilia-a classic marker of helminthic infection was absent, underscoring the diagnostic complexity in such immunocompromised hosts. This case highlights the critical need for heightened clinical suspicion of Strongyloides hyperinfection in high-risk populations such as chronic alcoholics, even in the absence of eosinophilia. Early diagnosis, aggressive management and consideration of atypical risk factors are essential to improving outcomes in this under recognized, but potentially fatal condition.